Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1021/es104322q
|View full text |Cite
|
Sign up to set email alerts
|

Catchment-Scale Quantification of Hyporheic Denitrification Using an Isotopic and Solute Flux Approach

Abstract: A dual-isotope and solute flux mass-balance was used to elucidate the processes that lead to attenuation of nitrogen contamination in an agriculturally impacted river. The River Wensum drains a lowland catchment with an area of 570 km² in East Anglia, eastern England. Analysis of nitrate concentration, δ¹⁵N(NO₃) and δ¹⁸O(NO₃) of samples from the River Wensum collected from upstream locations to the catchment outlet through all seasons and flow conditions showed a consistent pattern of increasing isotope values… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 46 publications
0
19
0
Order By: Relevance
“…As discussed above, isotopic fractionation can complicate their use for purposes of NO 3 − source identification because the original isotopic fingerprint of the source materials is altered. However, on the other hand, the nature and degree of isotope fractionation can also provide a powerful tool (Wexler et al 2011) for tracing N transformation processes.…”
Section: Utilization Of Stable Isotope Approach To Determine Nitrogenmentioning
confidence: 99%
“…As discussed above, isotopic fractionation can complicate their use for purposes of NO 3 − source identification because the original isotopic fingerprint of the source materials is altered. However, on the other hand, the nature and degree of isotope fractionation can also provide a powerful tool (Wexler et al 2011) for tracing N transformation processes.…”
Section: Utilization Of Stable Isotope Approach To Determine Nitrogenmentioning
confidence: 99%
“…The Chalk is exposed in the river valley and in the western catchment with nitrate concentrations often above 1000 lM (Taylor, 1984;Feast et al, 1998;Wexler et al, 2011). In the interfluves the Chalk is confined under the clay-rich Lowestoft Till with nitrate concentrations below the limit of detection (Feast et al, 1998;Wexler et al, 2011).…”
Section: Study Sitementioning
confidence: 99%
“…Dissolved nitrogen export is also subject to hydrological influences such as flow condition and baseflow index which expresses the proportion of mean river flow derived from stored groundwater as opposed to rainfall runoff. Denitrification within the hyporheic zone of the River Wensum has been shown to reduce the nitrate-nitrogen load exported from the Wensum catchment via the river by 31% (Wexler et al, 2011). Natural abundance stable isotopes of nitrogen and oxygen in nitrate are a powerful tool to track nitrogen cycling processes.…”
Section: Introductionmentioning
confidence: 99%
“…Further, these studies reported no isotopic effect during oxygen incorporations or any further isotopic exchange. Since then this concept has been widely used to understand and quantify microbial nitrate in the aquatic and sedimentary environment (Anisfeld et al, 2007;Ansari et al, 2012;Kendall, 1998;Tye and Heaton, 2007;Wexler et al, 2011 (10) (Buchwald and Casciotti, 2010;Kool et al, 2011;Snider et al, 2010;Spoelstra et al, 2007). This has certainly overcast the confidence in the traditional use of equation (10) (10) …”
Section: Stable Isotope Composition Of Microbial-nitratementioning
confidence: 99%
“…Among the 30 transported pollutants, nitrate has been a major focus for polar researchers due to its well known role in ozone chemistry (Crutzen et al, 1992;Solomon et al, 1996;Waibel et al, 1999) and acid rain events (KERR, 1979;SCHINDLER, 1988;Wright et al, 1988). However, the role of transported nitrate in the Arctic glacial ecosystem with changing glacial coverage remains understudied.…”
Section: Introductionmentioning
confidence: 99%